Coping among the caregivers of patients with schizophrenia - Sandeep Grover; Pradyumna; Subho Chakrabarti (Industrial Psychiatry Journal, 2015)
Coping is understood as the process of managing external or internal demands that are considered as taxing or exceeding the resources of the person. There is no formal classification of coping strategies, and these are understood as adaptive versus maladaptive and problem focuses versus emotion-focused. Understanding the commonly used coping strategies in a particular group of subjects can provide valuable insights for designing interventions to reduce the stress. In this review, we look at the literature which is available with regards to the coping strategies used by the caregivers of patients with schizophrenia. Findings suggest that caregivers of patients with schizophrenia use mixed type of coping mechanisms to deal with the stress of caregiving. The coping strategies are shown to have association with variables such as caregiver burden, caregiving experience, expressed emotions, social support, psychological morbidity in the caregivers, quality of life of caregivers and psychopathology in patients. One of the major limitations of the literature is that there is a lot of variability in the assessment instruments used across different studies to assess coping.